The behavior and transport of hydrogen in silicon solar cells observed through changes in contact resistance - Hamer, P; Li, H; Chan, C; Sen, C; Bonilla, R; Wilshaw, P (IEEE, 2018)
This paper presents a simple method of studying the transport of hydrogen in crystalline silicon, as well as its release from bound forms during annealing at temperatures between 350-450°C. This technique is based upon observations of an increase in the contact resistance of industrial solar cells, which displays the reversibility and dependence upon electric field commonly associated with hydrogen. It is shown that the increase in contact resistance depends strongly upon whether the device is fabricated on multi-or mono-crystalline silicon and upon the device structure.